Disciplining kids without screaming or scolding - Schrank, Louise Welsh; Helleren, Debra; Silk, Richard; Watt, Don; Learning Seed Company (Illinois : Learning Seed, 2007)
Paints a dramatic picture of the wrong way to discipline kids and gives clear, practical ideas on a better way. The program potrays destructive methods (shouting, verbal abuse, threats) followed by alternatives that focus on giving attention for positive rather than negative behaviour
Title from title screen
With English subtitles
Executive producer, Christine Schrank ; camera, Don Watt, Jon Ruffiner
Keywords: Discipline of children; Communication in the family; Parent and child